Dinosaur world - Bone , Emily (London : Usborne Publishing Ltd, 2020)
From the Tyrannosaurus Rex to the Triceratops - this book contains lots of interesting facts and statistics about different dinosaurs. Each page provides essential information such as the dinosaur's habitat, size, diet and plenty more 'did-you-know' facts for young minds to absorb. Satisfy young children's fascination with dinosaurs with this thorough yet easy to read introduction to the exciting world of dinosaurs. A fun addition to the popular Beginners series, with easy-to-read text and step-by-step visual explanations. It covers all kinds of fierce and not-so-fierce dinosaurs, along with how they died out, and how we know what they look like today
Keywords: Childern books